2020
DOI: 10.3390/agriculture10120579
|View full text |Cite
|
Sign up to set email alerts
|

Maize Yield Components as Affected by Plant Population, Planting Date and Soil Coverings in Brazil

Abstract: The potential yield of annual crops is affected by management practices and water and energy availabilities throughout the crop season. The current work aimed to assess the effects of plant population, planting dates and soil covering on yield components of maize. Field experiments were carried out during the 2014–2015 and 2015–2016 growing seasons at areas grown with oat straw, voluntary plants and bare soil, considering five plant populations (40,000, 60,000, 80,000, 100,000 and 120,000 plants ha−1) and thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Many authors indicate that the relationships occurring between plant traits revealed during ontogeny are better described by the method of path coefficient analysis (Szulc et al 2017;Aman et al 2020). Another method to determine the effect of individual plant yield components on differences in grain yield between two compared objects is proposed by Beruski et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors indicate that the relationships occurring between plant traits revealed during ontogeny are better described by the method of path coefficient analysis (Szulc et al 2017;Aman et al 2020). Another method to determine the effect of individual plant yield components on differences in grain yield between two compared objects is proposed by Beruski et al (2020).…”
Section: Discussionmentioning
confidence: 99%